The ALMaQUEST Survey X: what powers merger induced star formation?. Issue 1 (16th August 2022) - Thorp, Mallory D; Ellison, Sara L; Pan, Hsi-An; Lin, Lihwai; Patton, David R; Bluck, Asa F L; Walters, Dan; Scudder, Jillian M
ABSTRACT: Galaxy mergers are known to trigger both extended and central star formation. However, what remains to be understood is whether this triggered star formation is facilitated by enhanced star formation efficiencies (SFEs), or an abundance of molecular gas fuel. This work presents spatially resolved measurements of CO emission collected with the Atacama Large Millimetre Array (ALMA) for 20 merging galaxies (either pairs or post-mergers) selected from the Mapping Nearby Galaxies at Apache Point Observatory (MaNGA) survey. Eleven additional merging galaxies are selected from the ALMA MaNGA QUEnching and STar formation (ALMaQUEST) survey, resulting in a set of 31 mergers at various stages of interaction and covering a broad range of star formation rates (SFRs). We investigate galaxy-to-galaxy variations in the resolved Kennicutt–Schmidt relation, (rKS: $Σ _{H_2}$ versus ΣSFR ), the resolved molecular gas main sequence (rMGMS: Σ⋆ versus $Σ _{H_2}$ ), and the resolved star-forming main sequence (rSFMS: Σ⋆ versus ΣSFR ). We quantify offsets from these resolved relations to determine if SFR, molecular gas fraction, or/and SFE is/are enhanced in different regions of an individual galaxy. By comparing offsets in all three parameters, we can discern whether gas fraction or SFE powers an enhanced ΣSFR . We find that merger-induced star formation can be driven by a variety of mechanisms, both within a galaxy and between different mergers, regardless of interaction stage.